Study of psychological stress and acne vulgaris among pharmacy-students - Ab. Hadi, Hazrina; Awadh, Ammar Ihsan Jawad (Elsevier Inc., 2015)
OBJECTIVES: Acne vulgaris is described as a common skin disease involving blockage and inflammation of pilosebaceous unit such as hair follicles and sebaceous gland. As many factors may contribute to the formation of acne, this study attempt to provide an insight regarding interrelationship between the psychological stress as one of the contributing factor towards acne among final year pharmacy students at International Islamic University Malaysia. METHODS: This cross sectional study was conducted by distributing questionnaire among 98 final year students. Information on severity of acne and level of stress was collected by using the Global Acne Severity Scale (GEA) and the Perceived Stress Scale (PSS) which is a psychological test for assessing stress. RESULTS: The results obtained shows that there is positive correlation between acne vulgaris and stress, however it is not significant. The severity of the acne such as the open and close comedones, into papules, pustules, and nodules and even cysts are also related with several factors which may exacerbate the acne conditions. Among those factors are gender and family history, exposure to sunlight, diet, lifestyle such as sleep and exercise, skin condition, and also intervention in solving acne problem. CONCLUSIONS: In conclusion, there is a positive relation between acne vulgaris and stress. The acne condition exacerbates in more stressful conditions.